2019
DOI: 10.3390/app9214699
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Study of Coal Samples during Heating

Abstract: Raman spectroscopy can be used to record the characteristic spectra of carbonaceous materials. The D and G bands are the most popular and most important spectral characteristics when discussing carbonaceous materials. In this paper, a Raman spectroscopic study of different coals was first carried out using a 355 nm wavelength laser beam as an excitation source. The spectral parameters of the resultant spectra were evaluated and analyzed. Raman spectral characteristics of different kinds of coals were explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…In addition, in NiR AR, the bands at 1347 cm −1 and 1580 cm −1 , characteristic of disordered graphite (D band) and highly crystalline graphite (G band), respectively, were detected [86]. Usually, they are used to calculate the coke's disorder in spent catalysts and the size of the graphite microcrystals in the sample, as the ratio ID/IG relates to the average graphite domain dimension [87]. Those bands were observed only for spent alumina-supported catalysts, as shown in Figure 8 and Figures S2-S6.…”
Section: Catalyst Stabilitymentioning
confidence: 99%
“…In addition, in NiR AR, the bands at 1347 cm −1 and 1580 cm −1 , characteristic of disordered graphite (D band) and highly crystalline graphite (G band), respectively, were detected [86]. Usually, they are used to calculate the coke's disorder in spent catalysts and the size of the graphite microcrystals in the sample, as the ratio ID/IG relates to the average graphite domain dimension [87]. Those bands were observed only for spent alumina-supported catalysts, as shown in Figure 8 and Figures S2-S6.…”
Section: Catalyst Stabilitymentioning
confidence: 99%
“…For in situ investigations of char structure during the TCPs, the heating stage coupled with a micro-Raman spectrometer, as described in section , was mainly used. Xie et al , have applied this system to investigate the coal pyrolysis mechanism in Ar atmosphere from 298 to 1473 K. They compared the Raman spectra obtained in situ at high temperature with a 355 nm and a 532 nm laser as the excitation source, respectively. It was found that the background signal was very strong and can cover over the Raman bands when the 532 nm laser was used for detecting the coal sample with a temperature above 1037 K, and therefore, the 355 nm laser was suggested.…”
Section: Insitu Diagnostic During the Thermochemical Processmentioning
confidence: 99%
“…The changes in degree of graphitization of the as-received and treated anthracite were studied using Raman spectroscopy, and the spectrograms are presented in Figure 2. Though there seems to be some controversy regarding the assignment of various peaks to the graphitic and disordered structures in CM by different researchers, there are some consensus regarding the two most distinct peaks around wavelengths of 1580 cm -1 known as the graphite band (G), and 1370 cm -1 , the defect band (D) [32,33]. All the spectra showed three distinct bands at 1597 cm -1 and 1346 cm -1 , and 2500-3200 cm -1 for the aliphatic C-H functional groups.…”
Section: Raman Spectroscopy Studiesmentioning
confidence: 99%